Pencemaran Food Waste dalam Perspektif Undang-Undang Perlindungan dan Pengelolaan Lingkungan Hidup - Orias, Marco; Zaenal, Hery Kurniawan (Faculty of Law, University of Dr. Soetomo, 2023)
This research discusses the impact of food waste on the environment, especially in the context of environmental pollution and statutory regulations. This research provides practical understanding for the community about managing food waste so that it does not cause negative impacts. This research uses a case approach and a normative approach. In this research, it is stated that food waste contributes around 6% of total global greenhouse gas emissions. Waste management in Indonesia is still considered not optimal, with capacity in most districts/cities below 50%. With food waste, food waste disposal activities can produce methane gas, contributing to global warming. Environmental problems and the impact of food waste need to be addressed through legal approaches and public awareness. This research highlights the importance of adopting the circular economy concept and increasing the role of waste banks in waste management. However, it is still necessary to change overall waste management patterns to achieve a sustainable environmental balance.